2011
DOI: 10.1371/journal.pone.0027044
|View full text |Cite
|
Sign up to set email alerts
|

Structural Annotation of Mycobacterium tuberculosis Proteome

Abstract: Of the ∼4000 ORFs identified through the genome sequence of Mycobacterium tuberculosis (TB) H37Rv, experimentally determined structures are available for 312. Since knowledge of protein structures is essential to obtain a high-resolution understanding of the underlying biology, we seek to obtain a structural annotation for the genome, using computational methods. Structural models were obtained and validated for ∼2877 ORFs, covering ∼70% of the genome. Functional annotation of each protein was based on fold-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 56 publications
0
45
0
Order By: Relevance
“…Structural models of the Mtb proteome were obtained from a recent study by our group26. Crystal structures of 324 Mtb proteins available in PDB and 2737 comparative models that we generated in that study together account for about 70% of the proteome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural models of the Mtb proteome were obtained from a recent study by our group26. Crystal structures of 324 Mtb proteins available in PDB and 2737 comparative models that we generated in that study together account for about 70% of the proteome.…”
Section: Methodsmentioning
confidence: 99%
“…We also take advantage of the suite of computational algorithms that have been recently developed in our laboratory for binding site detection22, comparison2324 and functional characterization25. Using automated methods for comparing binding pockets2324, a first level function annotation was obtained in that study26. Here, we report (a) characterizing the pocketome to obtain proteome-wide ligand associations, (b) identifying number of pocket types present in Mtb proteome, (c) identifying clusters of similar pockets in the proteome, (d) estimating druggability among such pocket clusters and (e) identifying target sets with a polypharmacological potential.…”
mentioning
confidence: 99%
“…Automatically generated models using the Modeller package are made available in a dedicated database called MODBASE (31). For around 70% of the M. tuberculosis genome, structural models with reasonable confidence have been generated (17) (Fig. 1).…”
Section: Obtaining a Structural Proteomementioning
confidence: 99%
“…This approach has been utilized to obtain structural information for nearly 70% of the proteome (17). There are already a few excellent review articles on the structural biology of M. tuberculosis describing structural details of proteins involved in important biological processes (12,13,18,19).…”
mentioning
confidence: 99%
“…Previously, Schoonman et al have suggested that the threading methods are able to predict more accurate models than comparative modeling in cases of low sequence identity (<30%) [43]. Thus, based on the recent studies of successful implementation of threading approach [44][45][46][47][48][49], we carried out template search against the fold databases using several threading algorithms including PHYRE, FUGUE, pGenTHREADER, SAMT02, Genesilico, and Pcons metaservers. Amongst all the results of threading algorithms, only the mosquitocidal holotoxin from Bacillus sphaericus (2VSE) proposed by pGenTHREADER had similar secondary structure as that of Cyc2 with a value of 0.0006, SolvE score of −4.2, and net score of 48.983 amid a high confidence prediction range.…”
Section: Construction Of Cyc2 3dmentioning
confidence: 99%